Effect of cooling methods on dimensional accuracy and surface finish in reaming. (24th April 2019) - Islam, M.N.; Boswell, Brian
In recent years there has been limited research conducted into effectiveness of using minimum quantity lubrication (MQL) during reaming, when compared to other metal cutting processes. To establish the effectiveness of MQL for reaming a design-of-experiment (DOE) methodology was adopted. The three independent cutting conditions to ensure robustness of testing were MQL, dry and flood reaming. The quality evaluation criteria used for identifying effectiveness of the cooling method were diameter error, shape error, circularity and surface roughness (arithmetic average). The results were analysed applying Pareto ANOVA, signal-to-noise analysis and traditional analysis. Findings revealed that the cooling method used had a significant effect on surface roughness, shape error, diameter error, and a small effect on circularity. This research found that MQL reaming test results were similar to traditional flood cooling performance, confirming that MQL can replace flood reaming as it is a much more environmental method.